ANALISIS PEMANFAATAN SISTEM INFORMASI RUMAH SAKIT (SIMRS) PADA RS. IBNUSINA YW-UMI MAKASSAR - Radjab, Enny; Mandasari, Nur Fitriayu (Jurnal Paradigma, 2022)
The development of technological advances today is growing very rapidly. Currently, in various fields, an application sistem is needed which makes it a must and policy for every agency, both government and private, in data management that utilizes information as the basis for technology-based administration. The most important role in providing clinical services administratively with the use of information sistems must be owned by the hospital. At this time the management of information in hospitals has been implemented with the use of an electronic-based information sistem (SIMRS), every hospital requires a management information sistem (SIM) in improving the quality of medical services carried out. In an integrated hospital environment information sistem (SIMRS), the design of which can be used for all hospital activities into one integrated sistem so that it can be stored in a central database. The application of the use of applications that are stored in an existing case, data, and problems so that they can be turned into a new form without losing the basic values of the data, problems, and work itself.